A Study on Histopathological Spectrum of Lesions in Urinary Bladder Specimens - S, Susmitha; Patil, Girija S; Patil, S B (Annals of Pathology and Laboratory Medicine, 2018)
INTRODUCTION: Urinary bladder lesions constitute an important source of clinical signs and symptoms. Both non-neoplastic and neoplastic lesions are quite common. Neoplastic lesions are responsible for significant morbidity and mortality throughout the world. Urinary bladder cancer is 2nd most common cancer after prostate cancer in genitourinary system. Histopathological analysis of cystoscopic bladder biopsy and Transurethral resection of the bladder tumor (TURBT) material are the mainstay for cancer diagnosis. OBJECTIVE: To describe the histopathological spectrum of urinary bladder lesions in TURBT and cystoscopic biopsies. METHODOLOGY: All urinary bladder specimens were included in the study. The specimens were grossly examined and entire tissue was processed in all cases as per standard protocol. Multiple sections of 3-5 micron thickness were obtained and stained with H&E, followed by histopathological examination to classify them into non – neoplastic & neoplastic lesions on light microscopy. RESULTS: Total 48 cases were studied, out of which 20 were cystoscopic bladder biopsies and 28 were TURBT specimens. Non-neoplastic lesions was predominantly comprised of chronic non-specific cystitis. Among the neoplastic lesions, urothelial carcinoma is the predominant type and was most commonly seen in age group of 51-80 years constituting 92.85%. These neoplastic lesions were more common among males (71.43%) with M:F ratio of 2.5:1. Invasive urothelial carcinoma was the predominant type followed by various noninvasive urothelial lesions. CONCLUSION: Urinary bladder lesions are heterogenous and awareness regarding the various histological features of these lesions, their neoplastic potential, risk of recurrence and possible pitfalls can help pathologists for accurate diagnosis.